Pengaruh Trust, Perceived Risk, Moral Obligation terhadap Behavioral Intention pada Mahasiswa Pengguna ChatGPT - Mildah Rochmatul Laili Abin; Ruri Nurul Aeni Wulandari (Jumper: Journal of Educational Multidisciplinary Research, 2026)
This study was based on the inconsistency in behavioral intention to use ChatGPT repeatedly in an academic context. The study aimed to analyze the influence of trust, perceived risk, moral obligation, performance expectancy, effort expectancy, and social influence on behavioral intention among ChatGPT users who are Office Administration Education students from 2022 to 2024. This study is an explanatory research using a quantitative approach. This study employed multiple linear regression analysis. The findings indicate that trust, performance expectancy, effort expectancy, and social influence have a significant positive effect on behavioral intention; perceived risk has a non-significant positive effect on behavioral intention; and moral obligation has a non-significant negative effect on behavioral intention. Collectively, all predictor variables have a moderate effect on behavioral intention, accounting for 66.1% of the variance. These findings contribute to supporting the achievement of SDG 4 s(quality education) as assessed by the level of behavioral intention regarding the use of ChatGPT, to support assignments in courses on development of teaching materials and office communication